Operational evaluation of motor oils of trucks by their thermal oxidative stability - Hrynkiv, Andrii (Technology audit and production reserves, 2019)
The object of research is the process of determining the thermal oxidation of the working motor oil of trucks during their operation. One of the most problematic places is the establishment of appropriate oxidation regimes for working engine oil and the selection of the necessary laboratory equipment, as well as the formation of recommendations regarding the operational evaluation of the studied oils. The study used methods of thermal oxidation of samples of working engine oil in laminar mixing modes, as well as photometry to determine the degree of contamination with oxidation products. It is revealed that TEMOL Extra Diesel 15W-40, CF-4/CG engine oil in KamAZ 6520 cars (Russia) provides its functionality. At the same time, it is forbidden to change the mileage intervals for changing the oil under the prevailing operating conditions. Since on a mileage of 12.8 thousand km, the value behind the thermal oxidative stability of the oil during operation has a reserve of only 0.2 %, which is typical as critical. This is due to the fact that the proposed method for monitoring the condition of the working oil reflects the residual resource of oil of the specified brand in the studied range of trucks. It has been established that Rovas Truck 15W-40, CI-4/SN engine oil, which is used on MAN TGA 6×4 trucks (Germany), corresponds to operating conditions in terms of thermal oxidative stability. The operational margin for thermal oxidative stability of this brand of oil is 2.5 % for a range of 43.2 thousand km, which gives reason to expand the interval for its replacement by 1.1 thousand km of mileage. An increase in the resource of motor oil of the established brand is possible due to the determination of thermal oxidative stability, which also indirectly characterizes the performance of additives and the availability of the oil resource for the specified operating time. By determining the thermal oxidative stability of the oil, it is possible to provide a reasonable operational assessment of the working motor oil for the corresponding brand of the truck during their operation.